Diversity of Mollusks (Bivalvia and Gastropoda) in Medana Beach, North Lombok - Sasmitha, Yuan; Candri, Dining Aidil; Ahyadi, Hilman (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
Mollusks are an important group of marine organisms that contribute significantly to marine ecosystem structure and function, exhibiting high species diversity and widespread distribution across various marine habitats. Medana Beach, located in North Lombok, is a coastal area with ecological potential as a habitat for mollusks, particularly bivalves and gastropods. However, excessive exploitation beyond sustainable limits has led to a decline in mollusk populations, due to rates of harvest surpassing their natural regeneration. This study aims to assess the species diversity and community structure of mollusks (Bivalvia and Gastropoda) in the intertidal zone of Medana Beach. A purposive sampling method was used to select stations based on differing environmental characteristics, while transects were laid using systematic random sampling. Mollusk sampling, environmental parameter measurements (temperature, salinity, and pH), and substrate identification were carried out at all three study stations. A total of 55 mollusk species comprising 1,052 individuals were recorded, including 14 bivalve species and 41 gastropod species. The bivalves belonged to 9 families, and the gastropods to 17 families. The highest infaunal abundance was observed at Station 3 (616.67 ind/m³), while the highest epifaunal abundance occurred at Station 1 (15.38 ind/m²). Modiolus philippinarum had the highest infaunal density (255.56 ind/m³), found attached to seagrass roots in muddy-sand substrates. Cellana radiata had the highest epifaunal density (6.13 ind/m²), found attached to rocks. The mollusk community structure at Medana Beach was relatively stable, as indicated by moderate diversity and evenness indices, with no dominant species observed. These findings suggest that the habitat conditions at Medana Beach are capable of supporting mollusk communities and are not currently experiencing significant ecological stress.